Complications Connected to Late Diagnosis of Mandible Dentigerous Cyst - J. Andrejs; L. Tuček (Czech Dental Chamber, 2011)
Introduction: Dentigerous cyst is the second most often common odontogenic jaw cyst. It develops from epithelium of tooth source. Etiology and pathogenesis of dentigerous cyst are not clearly explained. By the time of formation cyst and evolution stage of handicapped tooth we distinguish three types of dentigerous cyst - cyst toothless, coronary and odontoblastic. Clinical demonstration can be absence of permanent tooth, curved alveolar process or change of teeth position. Diagnosis specify's roentgen examination, there is necessary histological verification to confirm diagnosis.Complications caused by presence of dentigerous cyst are connected to long term repression surrounding tissues over all (resorption of bone, tooth roots, lost of vitality surrounding teeth, fracture weaken mandible, sensitivity disorder in part nerve alveolaris inferior), less often with possibility of tumour development (most often in ameloblastoma) and at last also with possibility of cystic cavity infection, that is connected to infectional complication. The aim of case report: The aim of this notification is an effort to alert on prompt diagnosis of dentigerous cyst in time before complications that can make more difficult for following treatment and also can prolonged. As an example there are two case reports that describe complications of late recognized dentigerous cyst, in their most often placement, which is angle of mandible. The first patient had inficated cyst and development infectional complication, the second patient had iatrogenic fracture mandible during removing cyst.